Analysis of Tawarruq contract in the Islamic profit rate swap (IPRS) implementation in Malaysia. (20th September 2021) - Ahmad, Azlin Alisa; Mohd Dasar, Mohd Hafiz; Nik Abdul Ghani, Nik Abdul Rahim
Abstract : Purpose: This study aims to analyse the Shariah issues in the implementation of tawarruq contract in the Islamic profit rate swap (IPRS) instrument in Malaysia. Design/methodology/approach: This is a qualitative study in applying data analysis and semi-structured interview approaches. Data was collected from various documents including journals, articles and past studies conducted by scholars. To achieve the purpose of this study, the data is analysed based on thematic analysis. Findings: The study found several Shariah issues regarding the implementation of tawarruq contract in the IPRS instruments, which have remained a dispute amongst the Islamic financial scholars such as its profit-making purpose, encouragement of debt, impediment of shared risk concept, disputed underlying assets, a deception towards allowing riba and dual agency. Research limitations/implications: This study recommends several improvements such as the establishment of a neutral agency that does not represent any banking institution to manage the tawarruq contract commodity purchase from Bursa Suq al-Sila' (BSAS). In addition, a neutral agency can provide aid in terms of transaction facility or at least consultation service for clients to enable them to conduct the commodity transactions independently. Practical implications: Moreover, guidelines should be established on the separation of the deadline to sign the agreement of appointment of a bank as the commodity purchase agent and the agreement of appointment of the bank as the commodity sale agent on behalf of clients. All transactions related to tawarruq contract commodity must be done through BSAS. The regulators and industry experts may create a guideline for the IPRS based on the issues and recommendations that have been discussed in this study. Originality/value: On the basis of the analysis of the criticisms and issues in the implementation of tawarruq contract in the IPRS instrument, the current study found that an intermediating institution is allowed to gain profits from transactions conducted so long as they are based on Shariah principles of contract in Islam. As there is no parameter specifically for IPRS, thus the suggested parameter can be used by policymakers such as the Central Bank of Malaysia to ensure the industry complies with Shariah principles.